Taxonomic revision of the southernmost population of Hypostomus commersoni Valenciennes, 1836 (Siluriformes: Loricariidae) and comments on dispersal routes - Bertora, Andrea (2018)
Hypostomus is one of the most diverse genus of South American freshwater catfishes. InArgentina, Hypostomus commersoni Valenciennes, 1836 is distributed throughout the major rivernetworks of the La Plata River basin and in the Pampa Plain. The recent record of H. commersoni inthe Langueyú stream, represents the southernmost occurrence for this species and highlights therole of Samborombón bay as a likely dispersal route. It also supports the role of artificial channelsin the translocation of freshwater fauna. In this study, a taxonomic revision of H. commersoni fromthe Langueyú stream was performed and aspects about ichthyofauna dispersal routes are discussed.The taxonomy of populations in the extreme of the species´ distribution range contributes withinformation about geographic variation of characters.